2014
DOI: 10.1371/journal.pone.0095020
|View full text |Cite
|
Sign up to set email alerts
|

C-MYC Aberrations as Prognostic Factors in Diffuse Large B-cell Lymphoma: A Meta-Analysis of Epidemiological Studies

Abstract: ObjectivesVarious studies have investigated the prognostic value of C-MYC aberrations in diffuse large B-cell lymphoma (DLBCL). However, the role of C-MYC as an independent prognostic factor in clinical practice remains controversial. A systematic review and meta-analysis were performed to clarify the clinical significance of C-MYC aberrations in DLBCL patients.MethodsThe pooled hazard ratios (HRs) for overall survival (OS) and event-free survival (EFS) were calculated as the main effect size estimates. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 46 publications
(99 reference statements)
1
30
0
2
Order By: Relevance
“…19,22,35,[41][42][43] However, subsequent studies showing that MYC rearrangements were associated with BCL2 or BCL6 translocations (DH) in high numbers of cases (58% to 83%) suggested that the poor prognosis of MYC rearrangements could in fact caused by the synergistic action of these concomitant alterations and not by MYC aberrations alone. 20,22,35,41,43 The question whether MYC alterations by themselves may influence the evolution of the tumor is still controversial. Two recent studies have shown that single MYC translocations without BCL2 or BCL6 rearrangements have a similar poor prognosis to cases with DH, even in R-CHOP-treated patients, and tend to occur in older patients with advanced clinical stage, higher International Prognostic Index, and more frequent extranodal involvement.…”
Section: Clinical Impact Of Myc Alterations In Dlbclmentioning
confidence: 99%
See 1 more Smart Citation
“…19,22,35,[41][42][43] However, subsequent studies showing that MYC rearrangements were associated with BCL2 or BCL6 translocations (DH) in high numbers of cases (58% to 83%) suggested that the poor prognosis of MYC rearrangements could in fact caused by the synergistic action of these concomitant alterations and not by MYC aberrations alone. 20,22,35,41,43 The question whether MYC alterations by themselves may influence the evolution of the tumor is still controversial. Two recent studies have shown that single MYC translocations without BCL2 or BCL6 rearrangements have a similar poor prognosis to cases with DH, even in R-CHOP-treated patients, and tend to occur in older patients with advanced clinical stage, higher International Prognostic Index, and more frequent extranodal involvement.…”
Section: Clinical Impact Of Myc Alterations In Dlbclmentioning
confidence: 99%
“…These cases are often described as "double expression lymphoma" and have a worse prognosis than cases with overexpression of only one of the two proteins. 19,[33][34][35]43 Intriguingly, whereas the poor prognosis of double expression lymphoma cases is concordant in all studies, the independent impact of BCL2 or MYC protein expression is controversial. 19,34,35 The lack of reproducibility of these studies may be partially explained by the different cut-offs and non-standardized methods used to evaluate the tumors.…”
Section: Clinical Impact Of Myc Alterations In Dlbclmentioning
confidence: 99%
“…A number of genetic abnormalities are found in DLBCL including overexpression of BCL2 and BCL6. The MYC gene (8q24) is rearranged in 5–15% cases and is associated with very aggressive disease 20 . Particularly aggressive subtypes of DLBCL are the so-called ‘double-hit’ lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…2 MYC/8q24 rearrangement occurs in approximately 5% to 14% of cases. [3][4][5] Although genetic rearrangements usually in the form of translocations involving these genetic loci often occur as single abnormalities in DLBCL, they are not mutually exclusive and can occur in the same tumor. A number of studies have been published on so-called double-hit lymphoma (DHL) in which MYC rearrangements occur with another oncogene rearrangement in the same tumor.…”
mentioning
confidence: 99%